Peta Digital Kependudukan Berbasis QGIS: Inovasi Teknologi untuk Visualisasi Data kependudukan dan Populasi di Dusun Mrisi, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Wahyu Widodo; Emil Adly; Martyana Dwi Cahyati; Anna Nur Nazilah Chamim; Bunsa Jondan Satriawan; Ilham Rizki Saputra; Muhammad Ivan Mareza Pangestu; Trio Yonathan Teja Kusuma (Universitas Muhammadiyah Semarang, 2024)
Digital mapping has become a valuable tool for managing and visualizing geographical information. In this context, this community service aims to create a digital map using WebGIS in Mrisi Hamlet. Mrisi requires accurate and efficient mapping of population data to optimize data collection methods. This is to make decisions related to regional development, and map resources such as UMKM. This activity method involves collecting spatial and attribute data through field surveys, remote sensing, and relevant secondary data sources. The data obtained is then processed and compiled into a web-based geographical information system. In developing digital maps, WebGIS was chosen because it provides easy accessibility, interactive data visualization, and the ability to share geographical information with other users. This activity results in a digital map that includes various relevant information about Mrisi Hamlet. The map includes area boundaries, infrastructure, land use, public facilities location, and other related information. These digital maps are internet-based access and use decision-making by local governments, communities, and other related parties.